B is for BDSM: 13 Erotic Short Stories - Curant, Catrina (Saga Egmont, 2023)
'B is for BDSM: 13 Erotic Short Stories' is a collection of erotica that explores the sexual and sensual pleasures of BDSM from being tied up to your master's mercy, from lesbian liasons to your deepest fantasies, explore the depths of BDSM.